(untitled) (Pedagogy of Higher and Secondary Education, 2021)
The article reviews the common approaches to the method as a scientific concept to the structure of cognitive process. The emergence of scientifically based methods knowledge (a methodology as a system of principles and methods of organizing and building a theoretical and practical activities) is the result of creative achievements of thinkers of different times, eras, nations. Their product is the nature of the method, its basis, functions.